Cleaner isolation and application of sustainable new novel source of natural dye from tallow laureal (Litsea glutinosa) for silk dyeing - Fazal‐ur Rehman; Muhammad Abdul Qayyum; Kinza Zainab; Shahid Adeel; Noman Habib; Rony Mia; Muhammad Imran; Sidra Nasir (Energy Science & Engineering)
Abstract The utilization of waste plant residues in useful work particularly as the source of green dyes in textiles is now a days welcoming by global community. In this study, brown bollygum chips (Litsea glutinosa) called tallow laurel has been explored for silk dyeing using ecofriendly approaches. Extraction has been done in suitable medium and utilized onto fabric before and after microwave (MW) treatment up to 10 min. Response surface methodology was employed to observe the significant of selected dyeing parameters at which shade development with improved colorfastness was observed. It was found that 2 min radiation to both acidic extract of tallow laureal and silk fabric is the useful condition to get colorfast shade when employed before and after mordanting with iron salt and tannic acid solution as eco‐chemical agent, whereas with walnut bark and pine nut hulls extract as eco bio agents. The highest color strength value of 4.58 was observed using tannic acid as postchemical mordant for silk dyeing. The standard methods for fastness as per ISO to light, washing, and rubbing reveal that using selected shades made under ecofriendly cost time and energy effective conditions, stable colorfast hues were rated good with the value of 4/5. Therefore, it is recommended that MW treatment in addition with statistical approach i.e., central composite design used for exploring new dye yielding plant, then using eco‐mordanting technique will help in getting promising colorfast shades.